CELSTIAL MAIDEN WIFE TALES (TENNIN NYŌBŌ-TAN) IN THE AMAMI ISLANDS: Localization of Swan-Maiden-type Legends - Iwase, Hisami; Yoneda, Mayumi (Universitas Negeri Surabaya, 2025)
The celestial maiden wife tales (Tennin Nyōbō-tan) told in Japanese Amami Islands correspond to the globally recognized Swan Maiden type. These narratives typically describe a celestial maiden whose flying garment is taken by a man, forcing her to become his wife. Amami versions exhibit distinctive features: origin legends in which the celestial maiden’s daughter becomes a noro (priestess) or yuta (female shaman); lullabies that reveal the hidden location of the hagoromo and found in many versions; and performances of the tale as kuduchi (kudoki - narrative songs) which are still sung today. The regional image of the celestial maiden or amore onagu is multivalent, encompassing religious figures, social outsiders, and ghosts. Furthermore, influences from performing arts and folktales of Okinawa are also evident in the transmission of these tales. Drawing on 42 orally collected and published texts, the analysis employs motif comparison and textual interpretation to illuminate the layered imagery and oral aesthetics of Amami’s Tennin Nyōbō-tan. In doing so, it contributes to understanding how oral tradition and performance localize a global folktale motif.